2019
DOI: 10.1007/s42452-019-1093-0
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and environmental investigation of sewage-irrigated soils and crops of Sabzevar, NE of Iran

Abstract: The present study identifies the effects of sewage irrigation on the surface soils geochemistry and the concentration of heavy metals in plants of Sabzevar area, which were irrigated for a long time by wastewater. This study shows that the sewage irrigation has led to decreasing pH and increasing organic matter, and also it makes the accumulation of P 2 O 5 , high-field-strength elements (Ga, Ta, Th, U and Y) and heavy metals (Cd, Co, Cu, Pb, Sn and Zn) in contaminated soils. Likewise, the concentration of rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…With the exception of Ni and Pb in Annona senegalensis, Magnifera indica, and Psidium guajava, concentrations of these heavy metals were several folds above their corresponding WHO maximum permissible limit in medicinal plants. This observation is in agreement with the previous studies that reported elevated total heavy metal concentrations above WHO maximum permissible limits in medicinal plants [53,54]. Among these heavy metals, As, Cd, Hg, and Pb are considered out-rightly toxic metals and ranked among the priority metals that are of public health significance because they do not have any known biochemical and physiological functions and are known to induce multiple organ damage, even at very low levels of exposure [55][56][57][58].…”
Section: Discussionsupporting
confidence: 92%
“…With the exception of Ni and Pb in Annona senegalensis, Magnifera indica, and Psidium guajava, concentrations of these heavy metals were several folds above their corresponding WHO maximum permissible limit in medicinal plants. This observation is in agreement with the previous studies that reported elevated total heavy metal concentrations above WHO maximum permissible limits in medicinal plants [53,54]. Among these heavy metals, As, Cd, Hg, and Pb are considered out-rightly toxic metals and ranked among the priority metals that are of public health significance because they do not have any known biochemical and physiological functions and are known to induce multiple organ damage, even at very low levels of exposure [55][56][57][58].…”
Section: Discussionsupporting
confidence: 92%
“…The order in the pumpkin was Zn > Cu > Ni > Co > Cd > Pb indicating that metals accumulate differently in some plants. Mazhari et al (2019) conducted a study on the geochemical and environmental investigation of soils and crops and reported concentrations of Cr, Cu, Ni and Pb exceeding maximum permissible levels in alfalfa and maize crops. Some of the studies have investigated the human health risks associated with vegetables grown on soil irrigated with treated wastewater (Gupta et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The risks of As and Pb in the Indian rice and the Cd in Iranian rice are signi cantly higher than other types. Contamination of the consumed rice can increase the concentration of toxic metals in the maternal blood(Shara et al 2019).A study in Sabzevar disclosed that the concentration of toxic metals in agricultural products irrigated by e uent wastewater was higher than the maximum permitted level(Mazhari et al 2019). These toxic metals can enter the food chain through bioconcentration and bio-magni cation phenomena(Martí-Cid et al 2008).…”
mentioning
confidence: 99%